(untitled) (Movimenta (ISSN 1984-4298), 2022)
INTRODUCTION: In Brazil, 23.9% of the total population has some type of visual, hearing, motor or intellectual disability. Of these, 7.53% are children aged 0 to 14 years who show some type of disability. Several conditions such as down syndrome, cerebral palsy and spina bifida can accompany children and their ability to move and engage in self-directed mobility. OBJECTIVE: Identify the potential benefits and barriers of implementing motorized mobility. METHODS: A narrative and comprehensive review of scientific articles on the proposed topic was carried out. The search was conducted in the databases PubMED, MEDLINE and Physiotherapy Evidence Database (PEDro), from June to August 2021. The descriptors used in the search were: children, mobility, early motorization, motorized mobility. RESULTS: After reading the abstracts, 13 articles were excluded, and after critical reading and analysis of the materials, 12 articles were selected, of the 12 requested, 4 were excluded because they did not address the topic, leaving 8 articles for a review. CONCLUSION: Motorized cars adapted for children with a walking disorder are viable and fun, with benefits to gain mobility and socialization. The main limitations are related to the development of studies with specific methodology and criteria. Studies involving motorized mobility are feasible and well accepted by the community. The use of motorized mobility has benefits for mobility and socialization. The main barriers found were environmental barriers.